Midterm survival and risk factor analysis in patients with pyogenic vertebral osteomyelitis: a retrospective study of 155 cases - Schindler, Melanie; Walter, Nike; Reinhard, Jan; Pagano, Stefano; Szymski, Dominik; Alt, Volker; Rupp, Markus; Lang, Siegmund (Frontiers in Surgery, 2024)
Background: Pyogenic vertebral osteomyelitis (VO) represents a clinical challenge and is linked to substantial morbidity and mortality. This study aimed to examine mortality as well as potential risk factors contributing to in-hospital mortality among patients with VO. Methods: This retrospective analysis involved patients receiving treatment for VO at University Regensburg in Germany from January 1, 2000, to December 3, 2020. It included in-hospital mortality rate, comorbidities and pathogens. Patients were identified using ICD-10 diagnosis codes: M46.2, M46.3, M46.4, and M46.5. Kaplan–Meier probability plots and odds ratios (OR) for mortality were calculated. Results: Out of the total cohort of 155 patients with VO, 53 patients (34.1%) died during a mean follow-up time of 87.8 ± 70.8 months. The overall mortality was 17.2% at one year, 19.9% at two years and 28.3% at five years. Patients with congestive heart failure (p=0.005), renal disease (p<0.001), symptoms of paraplegia (p=0.029), and sepsis (p=0.006) demonstrated significantly higher overall mortality rates. In 56.1% of cases, pathogens were identified, with Staphylococcus aureus (S. aureus) and other unidentified pathogens being the most common. Renal disease (OR 1.85) and congestive heart failure (OR 1.52) were identified as significant risk factors. Conclusion: Early assessment of the specific risk factors for each patient may prove beneficial in the management and treatment of VO to reduce the risk of mortality. These findings demonstrate the importance of close monitoring of VO patients with underlying chronic organ disease and early identification and treatment of sepsis. Prioritizing identification of the exact pathogens and antibiotic sensitivity testing can improve outcomes for patients in this high-risk group.